2022
DOI: 10.1155/2022/2938380
|View full text |Cite|
|
Sign up to set email alerts
|

Safety and Efficacy of Unicondylar Knee Prosthesis Treatment for Unicompartmental Osteoarthritis of the Knee Joint

Abstract: Background. Knee osteoarthritis (KOA) is a chronic disease that seriously endangers the health of the elderly. Choosing appropriate surgery for knee osteoarthritis patients is especially important. Objective. To investigate the safety and efficacy of unicondylar knee prosthesis treatment for unicompartmental osteoarthritis of the knee. Materials and Methods. One hundred patients with unicondylar osteoarthritis of the knee treated in our hospital from June 2019 to June 2021 were selected as retrospective study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: The presence of these indicators undermines our confidence in the integrity of the article's content and we cannot, therefore, vouch for its reliability.…”
mentioning
confidence: 99%